Asymptotic behavior of a diffusive eco-epidemiological model with an infected prey population - Wonlyul Ko; Wonhyung Choi; Inkyung Ahn (Advances in Difference Equations, 2017)
Abstract We study a diffusive predator-prey system with a ratio-dependent functional response when a prey population is infected under homogeneous Neumann boundary condition. All non-negative and positive equilibria are investigated, and the conditions that give rise to asymptotic behavior of these equilibria are examined. In particular, we present a biological interpretation of disease-free and total extinction states. A comparison principle and the stability analysis for the parabolic problem are employed.